Electrochemical impedance spectroscopy for analyzing microstructure evolution of NaA zeolite membrane in acid water/ethanol solution. (22nd October 2016) - Cai, Xianshu; Zhang, Yuting; Yin, Liangwei; Ding, Dandan; Jing, Wenheng; Gu, Xuehong
Abstract: NaA zeolite membrane exhibits high separation performance in dehydration of organics. However, the structural stability of NaA zeolite membrane is a critical issue for large-scale applications. In this study, electrochemical impedance spectroscopy (EIS) was first adopted to reveal the microstructure evolution of NaA zeolite membrane. Pervaporation separation of NaA zeolite membranes in acid water/ethanol solution was investigated for comparison. The permeation flux decreased initially and then increased while the separation selectivity declined continually. SEM, EDS and XRD characterizations showed structural degradation of NaA zeolite membrane layer in acid environments. Electrochemical impedance of NaA zeolite membrane was measured in acid solutions. The variation trend in the electrochemical impedance was found to agree well with that for separation performance caused by microstructure evolution. An equivalent circuit model was also constructed to evaluate electrical properties of the membrane system. Graphical abstract: Highlights: EIS was developed to study microstructure evolution of NaA zeolite membrane. An equivalent circuit model was built to analyze impedance spectra. The variation of electrochemical property agreed well with pervaporation results.